Determinação da acidez total de vinhos tintos empregando titulações baseadas em imagens digitais - Tôrres, Adamastor Rodrigues (2010)
This work proposes the use of digital images captured by a Webcam for determination of total acidity in red wines by means of an acid-base titration without using an external indicator. Digital images present the colour of the emergent radiation, which is complementary to the radiation absorbed by molecules of anthocyanines presents in wines. Each image, generated according to RGB system, yields a matrix of the values of the R, G and B components whose averages define a the colour value obtained as: 2R ⋅2G ⋅2B. This value was adopted as analytical response to build titrations curves based on digital images (DIB). For a more precise localization of the end point, titrations curves were generated on the basis of the second derivative values of the analytical response. Anthocyanines present different colours according to medium pH and, from the variation of the colour values of the images obtained during the titration of the red wines, the end point could be detected with precision. The official method recommends the use of potenciometric titration for determination of total acidity in red wines. This method requires a dilution of the sample before the titration that must be carried out until a fixed value of pH (8.2 8.4). In order to illustrate the feasibility of the proposed method titrations involving the determination of total acidity in ten red wines samples were carried out. Results were compared to the ones obtained by potenciometric titration used as reference method. No statistic difference has been observed between the results by applying the paired t-test at 95% confidence level. The proposed method yielded results with a better precision than the official method. These advantageous characteristics are attributed to the trivariate nature of the measures associated to digital images.